FIRM VALUE DETERMINATION WITH INFLATION AND EXCHANGE RATE AS A MODERATING VARIABLE (Study on the Manufacturing Industry Recorded in Indonesian Sharia Stock Index) - Soekapdjo, Soeharjoto (The International Journal of Accounting and Business Society, 2021)
Purpose - Aims of this study is to determine the factors that influence the firm value of manufacturing industry listed on ISSI. Design/methodology/approach - Used panel data regression method from 2013-2018, than obtained 30 manufacturing industry companies after purposive sampling. Syariah stock investors who rationally and religiously behave are accommodated in the variables used. Dependent variable is firm value and independent variable are ROE, CR, DER, TATO, ISR, with exchange rate and inflation as the moderating variable. Finding - Result shown that ROE with inflation as a moderating variable have a positive effect on firm value. ISR has a positive effect on firm value. DER with the exchange rate as a moderating variable has a negative effect on firm value. CR and TATO are not significant to firm value. Practical Implication - To increase the firm value, it is necessary to improve human resources and the application of environmentally friendly technology, planning in production and expansion, transparency and application of sharia principles, professional and fair managers. Originality/value - This study combines company’s financial ratios, ISR and macroeconomic condition that beyond management control. Tobins’ Q is used to corporate values approach. All of these, reflect that firm value is influenced by company performance, society, government and blessing from Allah SWT.